An ethanol extract of Poria cocos inhibits the proliferation of non-small cell lung cancer A549 cells via the mitochondria-mediated caspase activation pathway - Bo-Feng Chu; Hang-Ching Lin; Xin-Wen Huang; Han-Yu Huang; Carol P. Wu; Ming-Ching Kao (Journal of Functional Foods, 2016)
Poria cocos, a food ingredient and a traditional Chinese medicine, is a fungus commonly used in eastern countries. It exhibits diuretic, anti-inflammatory, immunomodulatory and anti-hyperglycaemic functions. In addition, the polysaccharide and triterpenoid components isolated from P. cocos exhibit anti-tumour effects in a number of cancer cell lines. Here, an extract of P. cocos, designated H287, was evaluated for its anti-lung cancer potential. H287 induced apoptosis in A549 cells via the mitochondria-mediated caspase activation pathway, as demonstrated by the loss of mitochondria outer membrane potential, release of cytochrome c into the cytosol, and the cleavage of procapsase-9 to caspase-9. Further analyses suggest that tumulosic acid, one of the triterpenoids present in H287, is responsible for the cytotoxic function of H287. H287 may potentially serve as a dietary supplement or functional food ingredient for patients suffering from non-small cell lung cancers.